Does the fatigue loading frequency affect the lithium disilicate glass ceramic inlay-dentin bond strength? - Trindade, Flavia Zardo [UNESP]; Campos, Fernanda [UNESP]; Marinho, Caroline Cotes [UNESP]; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe; Kleverlaan, Cornelis J. (Elsevier, 2018)
The aim of this study was to verify the effect of loading frequency during mechanical cycling on the microtensile bond strength between tooth and ceramic inlays. Twenty-four extracted permanent maxillary molars were standardly prepared (3 mm wide × 4 mm deep) to receive lithium disilicate-based ceramic inlays. After the adhesive cementation, the restored teeth were divided into three groups (n = 8), according to different range of mechanical cycling frequency: control group – water storage, 2.0 Hz group – mechanical cycling at frequency of 2.0 Hz (0–100 N, 1.2 × 106 cycles, water 37 °C), and 6.7 Hz group – mechanical cycling at frequency of 6.7 Hz (0–100 N, 1.2 × 106 cycles, water 37 °C). The teeth were then cut into microbars (1 × 1 mm, non-trimming method), which were tested under microtensile (MTBS) loading. The failure mode was classified and the data were analyzed by one-way ANOVA. The mean bond strength value of the control group was the highest and the values of the cycled groups were 15% lower, however the groups were statistically similar (p = 0.58). Chi-square test showed no statistical difference among the groups regarding the pre-test failures (p = 0.17). For all groups, the most frequent failure type was mode 1 (adhesive at the interface ceramic/cement) and mode 2 (mixed failure). Loading frequencies up to 6.7 Hz had no effect on the lithium disilicate glass ceramic inlay-dentin bond strength.
Keywords: Aging; Bond strength; Fatigue; Lithium disilicate; Micro-tensile